Immunomodulation by allograft endothelial cells - Bose, Sayantan; Do, Vicki; Testini, Chiara; Jadhav, Suchita S.; Sailliet, Nicolas; Kho, Alvin T.; Komatsu, Masaki; Boneschansker, Leo; Kong, Sek Won; Wedel, Johannes; Briscoe, David M. (Frontiers in Transplantation, 2025)
It is increasingly appreciated that the expression of immunoregulatory molecules within tumors have potential to shape a microenvironment that promotes local immunoevasion and immunoregulation. However, little is known about tissue-intrinsic immunomodulatory mechanisms following transplantation. We propose that differences in the phenotype of microvascular endothelial cells impact the alloantigenicity of the graft and its potential to promote immunoregulation following transplantation. We focus this review on the concept that graft-dependent immunoregulation may evolve post-transplantation, and that it is dependent on the phenotype of select subsets of intragraft endothelial cells. We also discuss evidence that long-term graft survival is critically dependent on adaptive interactions among immune cells and endothelial cells within the transplanted tissue microenvironment.